Factors Influencing Energy-saving Behavior of Air-conditioner Usage in Sanam Chandra Palace Campus, Silpakorn University - Khuwaranyu, Kittisak; Ruen-ngam, Duangkamol (Food Agricultural Sciences and Technology, 2019)
This research was aimed at identifying the individual factor, level of knowledge and attitude towards the energy saving on the air conditioner which affected behavior in using the air conditioner of students and staff in Silpakorn University, Sanam Chandra Palace campus. The research conducted the survey research and the findings was as follows: 1) The factors affecting the using behavior in energy saving of staff and students in Silpakorn university, Sanam Chandra Palace campus were gender, age, educational background, marital status, monthly income, function, and number of members in residence while the factors not affecting energy saving behavior was information awareness in energy saving 2) the level of knowledge and attitude in energy saving had relation to energy saving at statistical level of significance and 3) university student and staff had the high level of knowledge in energy saving intervention on air conditioner but had level of behavior at medium level.